2017
DOI: 10.1111/jpi.12420
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits neuronal dysfunction‐associated with neuroinflammation by atopic psychological stress in NC/Nga atopic‐like mouse models

Abstract: Atopic dermatitis (AD), also known as atopic eczema, is chronic pruritic skin disease. AD can increase psychological stress as well, increasing glucocorticoid release and exacerbating the associated symptoms. Chronic glucocorticoid elevation disturbs neuroendocrine signaling and can induce neuroinflammation, neurotoxicity, and cognitive impairment; however, it is unclear whether AD-related psychological stress elevates glucocorticoids enough to cause neuronal damage. Therefore, we assessed the effects of AD-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 85 publications
(179 reference statements)
0
41
0
Order By: Relevance
“…Hence, chronic GC elevation disturbs neuroendocrine signaling and can induce neuroinflammation, neurotoxicity, and cognitive impairment [ 106 ]. One study assessed the effects of AD-induced stress in a mouse AD model and the results have shown that AD-related PS increased astroglial and microglial activation, neuroinflammatory cytokine expression, and markers of neuronal loss [ 114 ].…”
Section: The Effect Of Stress In Ad On the Hpa Axismentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, chronic GC elevation disturbs neuroendocrine signaling and can induce neuroinflammation, neurotoxicity, and cognitive impairment [ 106 ]. One study assessed the effects of AD-induced stress in a mouse AD model and the results have shown that AD-related PS increased astroglial and microglial activation, neuroinflammatory cytokine expression, and markers of neuronal loss [ 114 ].…”
Section: The Effect Of Stress In Ad On the Hpa Axismentioning
confidence: 99%
“…Melatonin and its metabolites have been to be important for proper physiological skin function and effective protection of a cutaneous homeostasis from adverse environmental stimuli, and its use can attenuate hyperproliferative/inflammatory conditions [ 118 ]. Research has shown that administering melatonin inhibited skin lesions formation, scratching, and elevation of serum IgE levels in the murine AD stressed models [ 114 ]. Furthermore, it caused a significant reduction in CRH responsiveness, and a substantial decrease in neuronal damage [ 114 ].…”
Section: The Effect Of Stress In Ad On the Hpa Axismentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammation and neuroimmune signaling have been reported to be associated with neuronal dysfunction (Hong et al 2016; Park et al 2017). Thus, we tested inflammation-related gene expression in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was performed as described previously [12]. The dopamine content in the ST of the mouse brain was assessed using a commercially available fluorometric assay kit, following the manufacturer's protocol (Rocky Mountain Diagnostics, Colorado Springs, CO, USA).…”
Section: Western Blot and Determination Of Dopamine Content And Sodmentioning
confidence: 99%